2015
DOI: 10.1007/s11013-015-9475-2
|View full text |Cite
|
Sign up to set email alerts
|

“Thinking a Lot” Among the Khwe of South Africa: A Key Idiom of Personal and Interpersonal Distress

Abstract: “Thinking too much”, and variations such as “thinking a lot”, are common idioms of distress across the world. The contextual meaning of this idiom of distress in particular localities remains largely unknown. This paper reports on a systematic study of the content and cause, consequences, and social response and coping related to the local terms |x’an n|a te and |eu-ca n|a te, both translated as “thinking a lot”, and was part of a larger ethnographic study among the Khwe of South Africa. Semi-structured explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 31 publications
(64 reference statements)
1
27
0
Order By: Relevance
“…Respondents associated idioms of mental distress, especially those in the mind/brain category, as a precursor to psychoses and more severe mental illness if left untreated. This mirrors findings in mainland China, in which excessive thinking was perceived as a salient cause of schizophrenia; among the Khwe in South Africa, in which thinking a lot could lead to madness; in the Peruvian Andes, where the Quechua term pinsamientuwan , or worrying thoughts, can evolve into lukuyasca , or craziness; and in Haiti, where thinking too much was endorsed as leading to fou , or madness (Yang et al 2010; den Hertog et al 2016; Pedersen, Kienzler, and Gamarra 2010; Kaiser et al 2014). In this alternative explanatory model from the DSM and ICD, thinking too much is seen as a network of processes in which excessive negative rumination interacts with other psychopathological symptoms which can become progressively worse (Hinton et al 2016).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Respondents associated idioms of mental distress, especially those in the mind/brain category, as a precursor to psychoses and more severe mental illness if left untreated. This mirrors findings in mainland China, in which excessive thinking was perceived as a salient cause of schizophrenia; among the Khwe in South Africa, in which thinking a lot could lead to madness; in the Peruvian Andes, where the Quechua term pinsamientuwan , or worrying thoughts, can evolve into lukuyasca , or craziness; and in Haiti, where thinking too much was endorsed as leading to fou , or madness (Yang et al 2010; den Hertog et al 2016; Pedersen, Kienzler, and Gamarra 2010; Kaiser et al 2014). In this alternative explanatory model from the DSM and ICD, thinking too much is seen as a network of processes in which excessive negative rumination interacts with other psychopathological symptoms which can become progressively worse (Hinton et al 2016).…”
Section: Discussionsupporting
confidence: 62%
“…This usage of frustration may be unique to the Liberian setting, and suggests an alternative explanatory model for mental distress that is reminiscent of similar findings in SubSaharan Africa. (Yang et al 2010;den Hertog et al 2016;Pedersen, Kienzler, and Gamarra 2010;Kaiser et al 2014). In this alternative explanatory model from the DSM and ICD, thinking too much is seen as a network of processes in which excessive negative rumination interacts with other psychopathological symptoms which can become progressively worse (Hinton, Barlow, Ries, De Jong 2016).…”
mentioning
confidence: 99%
“…Reports from NGOs, staff at local clinic and community leaders indicate that HIV/AIDS and tuberculosis severely burden the communities, although statistics are not available. 16 , 17 Risk factors for STIs such as unemployment, alcoholism, domestic violence and HIV reported previously on marginalized communities in South Africa 18 were also entrenched among the Khwe and !Xun in Platfontein. 19 , 20 The San Baseline study conducted by the AIDS Foundation of South Africa revealed that 73% of the Platfontein San respondents were not using condoms, had multiple sex partners, and they had low knowledge of HIV and AIDS.…”
Section: Introductionmentioning
confidence: 87%
“…Where health services are available, often health staff do not speak their languages and are involved in the running of local services. 16 Based on the foregoing, we aimed to assess the knowledge and risk perceptions of STIs, HIV and AIDS in this indigenous population and their awareness of available local primary health care (PHC) services.…”
Section: Introductionmentioning
confidence: 99%
“…Culture-specific concepts or idioms of distress have gained much attention in the fields of cultural-clinical psychology and cultural psychiatry in recent years (den Hertog, de Jong, van der Ham, Hinton, & Reis, 2016; Hinton & Lewis-Fernández, 2010; Kirmayer, Gomez-Carrillo, & Veissière, 2017; Kohrt et al., 2014). Idioms of distress have been defined as an “embodied symbolic language for psychosocial suffering that derives its legitimacy from its shared metaphors, meaning and understanding in a group” (de Jong & Reis, 2010, p. 302).…”
Section: Introductionmentioning
confidence: 99%